2018
DOI: 10.4103/jos.jos_120_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of root length following treatment with clear aligners and two different fixed orthodontic appliances. A pilot study

Abstract: OBJECTIVES:The purpose of this pilot study was to evaluate the root lengths of upper incisors as an indication of the degree of orthodontically-induced apical root resorption following treatment with Smart Track® aligners and compare it with two different fixed orthodontic appliances – regular and Damon brackets – using cone-beam computerized tomography (CBCT).MATERIALS AND METHODS:The sample comprised 33 patients with class I malocclusion and 4–6 mm crowding divided in 3 groups; Group I: 11 patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 16 publications
3
43
1
2
Order By: Relevance
“…After eliminating duplicates, screening abstracts and reviewing full‐text articles, two studies were excluded after full‐text analysis because of the reasons followed: 1. no measurement of root resorption; 2. local or stage treatment (See ). As a result, 11 studies remained for qualitative analysis, whereas three studies were suitable for meta‐analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After eliminating duplicates, screening abstracts and reviewing full‐text articles, two studies were excluded after full‐text analysis because of the reasons followed: 1. no measurement of root resorption; 2. local or stage treatment (See ). As a result, 11 studies remained for qualitative analysis, whereas three studies were suitable for meta‐analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Since none of the included studies were RCTs, we used the ROBINS‐I tool to evaluate the risk of bias among the studies as one of the four levels (low, moderate, serious and critical). The overall result of the assessment showed that six studies presented a moderate risk of bias, while the other five were at serious risk of bias (Table ). The most problematic domains involved outcomes measurement, followed by deviations from intended interventions and confounding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations